The distribution function of the chord length of oval and ovaloid and its relation to distribution of a distance in an oval and ovaloid - Gečiauskas, E. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Гячяускас. Функция распределения длины хорды овала и овалоида и ее связь с распределением расстояния внутри овала и овалоидаE. Gečiauskas. Ovalo ir ovaloido stygos ilgio pasiskirstymo funkcija ir jos ryšys su atstumo pasiskirstymu ovale ir ovaloide